2013
DOI: 10.1007/s00421-013-2716-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metabolomics of muscle interstitium fluid in human trapezius myalgia: an in vivo microdialysis study

Abstract: PurposeThe mechanisms behind trapezius myalgia are unclear. Many hypotheses have been presented suggesting an altered metabolism in the muscle. Here, muscle microdialysate from healthy and myalgic muscle is analysed using metabolomics. Metabolomics analyse a vast number of metabolites, enabling a comprehensive explorative screening of the cellular processes in the muscle.MethodsMicrodialysate samples were obtained from the shoulder muscle of healthy and myalgic subjects that performed a work and stress test. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 78 publications
3
24
1
Order By: Relevance
“…For the sake of producing energy under the stress environment, tryptophan may resolve into carbohydrates. This result is in accordance with that reported in earlier studies of trapezius myalgia and chronic musculoskeletal pain (Hadrévi et al, 2013(Hadrévi et al, , 2015.We consider that the tryptophan-related metabolites found in this study may act as potent biomarkers of pain intensity in humans. In addition, a previous study showed that neural injury increased the production of monoamine by aromatic L-amino acid decarboxylase (Wienecke et al, 2014).…”
Section: Tryptophan Metabolismsupporting
confidence: 94%
See 2 more Smart Citations
“…For the sake of producing energy under the stress environment, tryptophan may resolve into carbohydrates. This result is in accordance with that reported in earlier studies of trapezius myalgia and chronic musculoskeletal pain (Hadrévi et al, 2013(Hadrévi et al, , 2015.We consider that the tryptophan-related metabolites found in this study may act as potent biomarkers of pain intensity in humans. In addition, a previous study showed that neural injury increased the production of monoamine by aromatic L-amino acid decarboxylase (Wienecke et al, 2014).…”
Section: Tryptophan Metabolismsupporting
confidence: 94%
“…As the result of the increase in gluconeogenesis, inhibitions in other amino acid metabolisms were also observed after the induction of hyperalgesia. This result is in accordance with that reported in earlier studies of trapezius myalgia and chronic musculoskeletal pain (Hadrévi et al, 2013(Hadrévi et al, , 2015.We consider that the tryptophan-related metabolites found in this study may act as potent biomarkers of pain intensity in humans.…”
Section: Tryptophan Metabolismsupporting
confidence: 94%
See 1 more Smart Citation
“…Since it is not clear how well blood plasma metabolite patterns reflect muscle metabolism, condition-and rat-matched IF and plasma metabolomics patterns were compared. Although there is at least one example of metabolomics analysis of muscle IF (15), to our knowledge, no experiments that used this approach in an acute exercise paradigm have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Lactate and pyruvate, products of cell glycolysis has, with divergent results, been examined in muscle interstitium in painful and pain free muscles [79][80][81][84][85][86][87][88]. Lactate has a complex physiological function as it can be produced during anaerobic and aerobic conditions and can be metabolized in the same cell or transported to other cells for metabolic use [89,90].…”
Section: Pain Physiologymentioning
confidence: 99%